Family business during the COVID-19 pandemic in Asia: Role of government financial aid and coping strategies - Wataru Kodama; Trinh Quang Long; Dina Azhgaliyeva; Peter J. Morgan; Kunhyui Kim (Asian Development Bank Institute (ADBI), 2023)
The COVID-19 pandemic has badly affected economic activities. In emerging Asia, where small family businesses play central roles in their economies, previous studies found that the sector was hit particularly hard by the pandemic. However, little is known about how households have mitigated the negative shocks on their family business during the pandemic. Using datasets from representative household surveys in 17 Asian countries from the Association of Southeast Asian Nations (ASEAN) and the Central Asia Regional Economic Cooperation (CAREC) regions, this study investigates the role of coping strategies and government financial aid in mitigating the adverse impacts of the pandemic on family business conditions in the short run. We find that: (i) coping strategies such as "switch products," "increase use of phone calls/sms," and "reduce price/offer promotion" are associated with a lower probability of a decline in income from a family business and/or family business closure; and (ii) government financial aid is associated with a lower probability of a decline in family business income and a higher probability of adopting coping strategies. This study is one of the first to provide empirical evidence on mitigation mechanisms of business households in emerging Asia, which is important to encourage a recovery of the family business sector from the pandemic.
Keywords: D1; H3; M2; 330; COVID-19; family business; coping strategy; financial aid; Central Asia; Southeast Asia